Gift Recommendations Based on Personality Using Fuzzy and Big Five Personality Test - Susana Limanto; Vincentius Riandaru Prasetyo; Ni Wayan Gitaputri (Ikatan Ahli Informatika Indonesia (IAII), 2022)
Gifts are usually given to someone to strengthen a relationship or to motivate someone. However, givers often need help determining the appropriate gift for the potential recipient. On the other hand, many recipients are disappointed with the gifts received. This event can result in the relationship between the giver and recipient being disrupted or the motivational goal not being achieved. This research aims to develop a system to recommend gifts based on the recipient's personality. Gift recommendation is determined based on the recipient's personality because the recipient highly values gifts that match the recipient's personality. The system is built using the Fuzzy method, and the personality measurement tool used is the Big Five Personality Test. Fifteen pairs of respondents validated the system. The validation results show that 80% of respondents as gift-givers strongly agree that the system helps determine the appropriate gift for someone. In addition, 73.33% of respondents as gift recipients strongly agree that the gifts recommended by the system do not disappoint them.